Implementation of Pedestrian Facilities Maintenance Policy in Pekanbaru City - Situmorang, Patrio; As’Ari, Hasim (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Pedestrian pathways require proper maintenance because well-maintained facilities can enhance healthy lifestyles, reduce motor vehicle volume, and improve the quality of comfortable environments. Therefore, the government enacted Regional Regulation No. 2 of 2009 concerning traffic and public transportation. However, the reality on the ground shows that many pedestrians still do not feel comfortable using pedestrian facilities, enforcement of sanctions for pedestrian facility misuse is lacking, and many damaged pedestrian facilities are found such as potholed sidewalks, faded zebra crossings, and poorly maintained pedestrian bridges, which can disrupt pedestrian activities and also endanger passing motorists.In this study, the author employs the implementation theory by David C Korten (Haedar Akib, 2010), namely the theory of implementation suitability models which are reviewed from 3 indicators, including suitability between programs and beneficiaries, program suitability with organizations, and suitability of beneficiary groups (pedestrian communities) with organizations. This research uses qualitative research methods that are descriptive analysis, with data collection techniques from interviews, observations, and documentation. The results show that the implementation of the Pedestrian Facility Maintenance Policy in Pekanbaru City is still not in line with expectations and its implementation is not yet optimal. Constraints in the implementation of the Pedestrian Facility Maintenance Policy in Pekanbaru City, as seen from David Korten's theory, are: ineffective communication among policy actors and coordination with third parties or private companies has not been running well, inadequate budget, and low community participation, resulting in widespread misuse of pedestrian facilities